Learning organization as a moderator of the relationship between knowledge creation and adaptability in international joint venture - Alzahrani, S.K. (Serials Publications, 2017)
Parents companies establish international joint ventures to sustain their competitive advantages such as entering to new market place, gaining recourses and/or developing new products. Despite numerous benefits, the management of international joint ventures requires extensive attention and focus from the parent companies. Previous studies indicate that there have been evident increases in the rate of failure of joint ventures. Based on the assumption that organizational learning is both a function of knowledge creation and the capabilities for adapting rapidly to change in a volatile environment. This study conceptualized the moderator effect of Learning Organization variable on the relationship between knowledge creation with joint venture adaptability theories, this article has examined and validated this relationship. However, 790 questionnaires were distributed to 79 international Joint venture organizations from Petrochemical industry including (oil & gas) in Saudi Arabia, of the 790 surveys, 760 valid responses were returned. The results show that the size of the moderating effect is medium; consequently, this study confirms that Learning Organization moderates the relationship between Knowledge Creation and Firm Adaptability. © Serials Publications Pvt. Ltd.